and Colitis in a Renal Transplant Patient: A Case Report - Paola García-Padilla MD; Kateir Contreras MD; Paola Parra Serrano MD; Natalia Sánchez Leon MD; Oscar Lucero Pantoja MD (SAGE Publishing, 2022)
Chronic diarrhea is a common reason for consultation in renal transplant patients. Cytomegalovirus infection is the cause of chronic diarrhea of infectious origin in 50% of cases, but coinfection with tuberculosis is rare. We present the case of a renal transplant patient with chronic diarrhea, with a finding of left colon colitis and positive microbiological studies in biopsy for tuberculosis and cytomegalovirus . The patient received valganciclovir and anti-tubercular treatment with adequate evolution. Immunosuppressed patients may have diarrhea secondary to opportunistic infections; therefore, an algorithm for early diagnosis and treatment is recommended.